ANALISIS KUALITAS AIR SUMUR BOR DI KELURAHAN KLASABI DISTRIK SORONG MANOI KOTA SORONG (STUDI KASUS: KPR VICTORY PERMATA SAKTI) - Pamudjianto, Agung; Guntur, Abdul Haris M. (Casuarina: Jurnal Teknik Lingkungan, 2023)
Sorong City is a city that has an area of 1,105 km2, which is divided into 10 districts and 41 sub-districts, one of which is Klasabi Village, Sorong Manoi District, which has an area of 27.87 ha. Water is very important in everyday life; the earth's surface contains more water than land. Aquatic ecosystems are generally divided into freshwater, seawater, and brackish ecosystems. This research aims to analyze the water quality of drilled wells in Klasabi Village, Sorong Manoi District, according to PP No. 22 of 2021, Minister of Health No. 492/Menkes/Per/IV/2010, and KEPMENKES No. 907 of 2002. And to plan solutions for water Drilled wells can still be used for people's daily needs. This research uses the Storet method, which is carried out by comparing water quality data with quality standards that have been determined according to their purpose using a water quality test tool consisting of pH, turbidity, TDS, salt, DO, and Fe. Physical and Chemical Parameter Test Results: Only 25% entered the class I quality standard, where this point was the Klasabi 4 sample point, while 75% entered the class II, III, and IV quality standard criteria, where this point was the Klasabi 1, Klasabi sample point 2, and Klasabi 3 according to the quality standards of Government Regulation No. 22 of 2021 concerning the implementation of environmental protection and management.